ADAPTIVE POTENTIAL OF THE CARDIOVASCULAR SYSTEM OF MEDICAL STUDENTS ON THE BASIS OF LOAD TESTING - Martusevich, A.K.; Bocharin, I. V.; Guryanov, M. S.; Kashirina, A. O. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the adaptive potential of the cardiovascular system of medical students based on stress testing. Methods and structure of the study. 127 first-year male students of the Volga Research Medical University participated in the scientific experiment. The age of the subjects was 18-19 years. For ECG recording and analysis of hemodynamic parameters, including those characterizing heart rate variability, the Medical Soft sports testing system (MS FIT Pro variant, Russia) was used. As a tool for stress testing, physical exercises of the GTO complex were used. Results and conclusions. The informativity of the generated load testing algorithm in monitoring the adaptive reserves of systemic hemodynamics is demonstrated. The use of a functional test with two types of load in medical students generally indicated that they had an adaptive response to them. At the same time, a number of indicators demonstrate the tension of regulatory mechanisms, which can be considered as a prenosological state. In addition, the specificity of hemodynamic reactive patterns for the considered variants of physical activity was revealed.